Variation at the major facilitator superfamily ZIFL1 gene influences zinc concentration of barley grain - Dinsa, Girma Fana; Russell, Joanne; Steffenson, Brian; Halpin, Claire; Waugh, Robbie (Frontiers in Plant Science, 2025)
Food and nutritional security are global challenges exacerbated by an increasing human population and impacted by climate change. Barley is among the top cereal crops grown worldwide and is a strategic crop for food and nutrition security in several geographical domains. However, barley grains are generally limited in iron and zinc, two major micronutrient deficiencies affecting billions of people around the world, but particularly women and children in developing countries. One promising strategy to enhance crop micronutrient status is via biofortification, the identification and use of nutrient-rich natural variants in crop genetic improvement. Germplasm assessed as being rich in essential nutrients are used as parental materials in traditional breeding strategies. While simple in theory, directly assessing grain nutrient concentration as a phenotype in a crop breeding program is not trivial, particularly in lesser developed geographies. As an alternative, genetic diagnostics can simplify the identification of desirable progenies and accelerate the breeding process. Here we explored natural variation for grain zinc concentration within 296 Ethiopian and Eritrean barley landraces using a genome-wide association study. We found strong associations with two SNPs, both of which were located within the barley ortholog of a tonoplast-associated major facilitator superfamily (MFS) transporter gene, Zinc induced facilitator-like 1 (ZIFL1) of Arabidopsis thaliana (AtZIFL1). Sequence-based haplotype analysis of the barley gene (HvZIFL1) extended this association to a 153-162 bp deletion in a non-coding region. The favourable haplotype, associated with higher grain Zn concentration, was found in ~20% of Ethiopian and Eritrean barley germplasm. Markers are designed to the diagnostic SNPs for use as molecular diagnostics in breeding for genotypes with enhanced grain Zn.